Inteligencia artificial y redes neuronales - Ormeño, Sandro Alex (2023)
Describes concepts related to artificial intelligence that allow establishing solid criteria on issues related to art and design development. Artificial intelligence has become more than just a simple tool and is evolving at great speed, which makes it difficult for users to adopt it. However, this does not prevent it from establishing itself in our society, although the rules to avoid its abuse have not been defined. Understanding this technology will allow, from the perspective of the artist or designer, to take appropriate measures either as a user, educator or, in the best case, to influence legislation.